Subarachnoid Block in Prone Position for lower limb surgery - Baral, Bidur Kumar; Poudel, Puspa Raj; Regmi, Shubhash; Karki, Anuj Jung; Koirala, Pradip; Shah, Aashish (Journal of Nepal Health Research Council, 2021)
Subarachnoid block is a safe and effective regional anesthesia technique. It is usually carried out in sitting or lateral position but it can also be performed in prone position. Here we report two cases of flame burn over bilateral gluteal region extending to the posterior and lateral aspect of both thighs, who were planned for debridement and split skin grafting. Both patients had difficulty in siting and lying on either side of lateral position. We had administered subarachnoid block in prone position taking into consideration of patient’s comfort and the nature of the procedure. Both patients remained hemodynamically stable throughout the procedure and their post-operative periods were uneventful.Keywords: Burn; prone position; subarachnoid block